Integrasi Isu Energi Terbarukan dalam Pembelajaran Perubahan Energi untuk Meningkatkan Literasi Lingkungan: Tinjauan Literatur - Elia Putri; Hanna Aulia Siregar; Dahlia Harahap; Halimah Berliani; M. Za'far Tholib; R.R Misha Emyra; Riska Pradila (Jurnal Pendidikan dan Ilmu Fisika, 2026)
Global environmental crises, including global warming and climate change, demand a radical reorientation in science education to foster ecological awareness. This study aims to examine the integration of renewable energy issues within the "Forms and Changes of Energy" topic as a pedagogical strategy to improve students' environmental literacy and cognitive competence. Employing a systematic literature review method, this study analyzes various empirical findings related to the implementation of active learning models and digital technology media. The synthesis demonstrates that integrating renewable energy issues through active learning models, specifically Project-Based Learning (PjBL) integrated with STEM/STEAM, Socio-Scientific Issues (SSI), and the SETS approach, significantly enhances students' green behavior and ecological consciousness. Furthermore, interactive digital instruments, such as PhET simulations and Google Sites, effectively visualize abstract concepts, increase average cognitive scores (from 55.3 to 78.7), and stimulate Higher-Order Thinking Skills (HOTS). Additionally, combining PjBL with differentiated learning yields a high increase in climate change awareness, evidenced by an N-gain score of 0.70. This study concludes that a contextual and prudent transformation of physics education can effectively convert theoretical comprehension into concrete sustainable actions.